Rheumatic Diseases and Obesity: Adipocytokines as Potential Comorbidity Biomarkers for Cardiovascular Diseases - Scrivo, Rossana (Hindawi Publishing Corporation, 2013)
Inflammation has been recognized as a common trait in the pathogenesis of multifactorial diseases including obesity, where a low-grade inflammation has been established and may be responsible for the cardiovascular risk related to the disease. Obesity has also been associated with the increased incidence and a worse outcome of rheumatoid arthritis (RA) and osteoarthritis (OA). RA is characterized by systemic inflammation, which is thought to play a key role in accelerated atherosclerosis and in the increased incidence of cardiovascular disease, an important comorbidity in patients with RA. The inflammatory process underlying the cardiovascular risk both in obesity and RA may be mediated by adipocytokines, a heterogeneous group of soluble proteins mainly secreted by the adipocytes. Many adipocytokines are mainly produced by white adipose tissue. Adipocytokines may also be involved in the pathogenesis of OA since a positive association with obesity has been found for weight-bearing and nonweight-bearing joints, suggesting that, in addition to local overload, systemic factors may contribute to joint damage. In this review we summarize the current knowledge on experimental models and clinical studies in which adipocytokines were examined in obesity, RA, and OA and discuss the potential of adipocytokines as comorbidity biomarkers for cardiovascular risk.